Prevalence and correlates of microvascular complications among patients with diabetes mellitus: a cross sectional study - Kumar, Ashok; Singh, Ardaman; Tanwar, Vikram S.; Govil, Nikhil (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus is a metabolic disorder of multiple etiology, characterized by chronic hyperglycemia and associated with various microvascular, macrovascular and nonvascular complications leading to increasing morbidity and mortality. Microvascular complications are daibetes specific and their relation with associated comorbidities studied worldwide. To estimate the prevalence of microvascular complications in diabetic patients and to find their relation with various comorbid conditions. Methods: A total of hundred diagnosed patients of diabetes mellitus with age ranging from 18 to 75 years were enrolled in the study. Patients were assessed for the presence of microvascular complications and associated comorbidities. The effect of various comorbidities on frequency of microvascular complications was also determined. Data collected was statistically analyzed. Results: In this study, the mean age of the study group was 55.77±11.75 years. Mean age of onset of the disease was 48.89±11.50 years. Mean duration of the disease in the study group was 6.86±5.02 years. Diabetic retinopathy, neuropathy and nephropathy was found in 76%, 63% and 69% patients, respectively. Among patients with hypertension, 91.7%, 83.3%, and 81.7% cases were found to have retinopathy, neuropathy and nephropathy, respectively. The corresponding figures for those with comorbid IHD were 91.1%, 83.9% and 76.8% respectively whereas among patients with coexisting metabolic syndrome, 92.5%, 80.6%, and 79.1% were found to have retinopathy, neuropathy, and nephropathy, respectively. Conclusions: The most frequent microvascular complication reported by this study was diabetic retinopathy. comorbid conditions like hypertension, ischemic heart disease, and metabolic syndrome were associated with higher prevalence of microvascular complications in diabetic patients.